Biosecurity risk factors for highly pathogenic avian influenza (H5N8) virus infection in duck farms, France. Issue 6 (2nd July 2020) - Guinat, Claire; Comin, Arianna; Kratzer, Gilles; Durand, Benoit; Delesalle, Lea; Delpont, Mattias; Guérin, Jean‐Luc; Paul, Mathilde C.
Abstract: Highly pathogenic avian influenza (HPAI) subtype H5N8 outbreaks occurred in poultry farms in France in 2016–2017, resulting in significant economic losses and disruption to the poultry industry. Current evidence on associations between actual on‐farm biosecurity risk factors and H5N8 occurrence is limited. Therefore, a retrospective matched case–control study was undertaken to investigate the inter‐relationships between on‐farm biosecurity practices and H5N8 infection status to provide new insights regarding promising targets for intervention. Data were collected on 133 case and 133 control duck farms (i.e. the most affected species) located in one area of the country that was mostly affected by the disease. Data were analysed using Additive Bayesian Networks which offer a rich modelling framework by graphically illustrating the dependencies between variables. Factors indirectly and directly positively associated with farm infection were inadequate management of vehicle movements (odds ratio [OR] 9.3, 95% credible interval [CI] 4.0–22.8) and inadequate delimitation of farm and units (OR 3.0, 95% CI 1.6–5.8), respectively. Inadequate disposal of dead birds was instead negatively associated with the outcome (OR 0.1, 95% CI 0.0–0.3). The findings highlight that reinforcing farm access control systems and reducing the number of visitors are key biosecurity measures to control farm vulnerability to H5N8 infection and could help setting priorities in biosecurity practices to prevent outbreaks' re‐occurrence.